2022
DOI: 10.1002/adma.202200854
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Inorganic Ligand Replenishment Enables Bandgap Stability in Mixed‐Halide Perovskite Quantum Dot Solids

Abstract: unite solution processing with desirable optoelectronic properties such as tunable light emission and long carrier lifetimes and diffusion lengths. [9][10][11] The rapid development of mixed-halide CsPbBr x /I 3−x nanocrystals via compositional tuning has enabled an EQE of 20.3% in the red with a full-width at half maximum (FWHM) of 40 nm. [12] Unfortunately, they have yet to rise to match the operating stability of organic [13,14] and inorganic quantum dot [15,16] LEDs: device operating stability (T 50 ) to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
106
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 30 publications
0
106
0
Order By: Relevance
“…Cesium lead halide perovskite nanocrystals (NCs) have drawn significant attention due to their superior optoelectronic properties, which include their efficient luminescence and narrow emission peak that is spectrally tunable over the entire visible wavelength range. Since Kovalenko and co-authors established a simple hot injection synthesis method for CsPbX 3 (X = Cl, Br, or I) NCs in 2015, these all-inorganic perovskite NCs have emerged as an appealing class of materials for ultrahigh-definition display (via light-emitting diodes or LEDs), ,, lasing, , and photovoltaic applications. ,,, For all of these applications, it is important to be able to fine-tune the optical bandgap, and this is commonly achieved by mixing species in the halide site, such as Br/Cl for blue-emitters or Br/I for red-emitters according to the Rec. 2020 standard. …”
Section: Introductionmentioning
confidence: 99%
“…Cesium lead halide perovskite nanocrystals (NCs) have drawn significant attention due to their superior optoelectronic properties, which include their efficient luminescence and narrow emission peak that is spectrally tunable over the entire visible wavelength range. Since Kovalenko and co-authors established a simple hot injection synthesis method for CsPbX 3 (X = Cl, Br, or I) NCs in 2015, these all-inorganic perovskite NCs have emerged as an appealing class of materials for ultrahigh-definition display (via light-emitting diodes or LEDs), ,, lasing, , and photovoltaic applications. ,,, For all of these applications, it is important to be able to fine-tune the optical bandgap, and this is commonly achieved by mixing species in the halide site, such as Br/Cl for blue-emitters or Br/I for red-emitters according to the Rec. 2020 standard. …”
Section: Introductionmentioning
confidence: 99%
“…Back in the 1990s, 2D structure‐based perovskite materials achieved highly efficient LEDs at low temperatures (77 K) with an external quantum efficiency (EQE) of 2–4% and a maximum luminance of more than 10 000 cd m −2 at a drive voltage of 2.4 V. [ 6,7 ] However, electroluminescence at room temperature was underappreciated due to the occurrence of exciton annihilation. [ 8–11 ] In 2014, Snaith and Friend et al first demonstrated MAPbI 3− x Cl x ‐based NIR perovskite diodes under room temperature. [ 7,12 ] This achievement is a huge milestone, and set perovskite LEDs (PeLEDs) over the last years.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7,12 ] This achievement is a huge milestone, and set perovskite LEDs (PeLEDs) over the last years. [ 13 ] Currently, the highest EQEs of green PeLEDs [ 14 ] and red PeLEDs [ 9 ] have exceeded 28% and 24.4%, respectively, which are comparable to the conventional OLEDs and QLEDs. However, the red channel emitted at 630 nm for LED displays still lags behind than green analogue.…”
Section: Introductionmentioning
confidence: 99%
“…1–16 Only five years after the first demonstration of room-temperature electroluminescence (EL) from perovskite light-emitting diodes (PeLEDs), lead-based PeLEDs have already achieved an impressive set of achievements, 17 with the highest external quantum efficiency (EQE) of both green and red light-emitting perovskite diodes exceeding 24% to date. 18,19 However, the development of blue LEDs as a key optoelectronic component is lagging far behind that of green and red LEDs. Lead leakage may pose serious environmental and public health hazards due to the inherent toxicity of lead.…”
Section: Introductionmentioning
confidence: 99%